Analysis of the Supervisory Role of the Surabaya City Immigration Office on the Existence of Foreigners - I Gusti Ayu Dini Riarti Laretna Laksmi; Amirul Mustofa; Eny Haryati; Widyawati Widyawati (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to describe and analyze: the role of supervision and obstacles faced and the efforts made by the Surabaya Special Class I Immigration Office in its role to supervise the existence of foreigners. The research method to be used is qualitative descriptive. Data Collection Techniques include: Interviews, Observations, Documentation. The research informant is the Head of the Suarabaya Special Class I Immigration Office. The data analysis technique using interactive model analysis was developed by Miles et al., (2014), namely data condensation, data presentation, and conclusion drawn. The results of the study show that the Surabaya Special Class I Immigration Office has three roles in supervising foreigners, namely as an immigration facilitator on duty, including providing residence permit and immigration status services, determining immigration status for foreigners in Indonesia, conducting research on the correctness of a person's citizenship evidence. As an Administrator in the supervision of foreigners, it is carried out through administrative supervision when a foreign citizen submits an application to the Immigration Office. As an Executor in the supervision of foreigners, it is carried out by 1) searching for and obtaining information about the existence of Indonesian citizens who are outside Indonesian Territory; 2) Conduct an interview when applying for a Travel Document of the Republic of Indonesia; or 3) Coordinate with the local government through the Chief Representative of the Republic of Indonesia to monitor the existence of Indonesian citizens outside the Indonesian Territory. The obstacles faced by the Surabaya Special Class I Immigration Office include the range of work which includes Surabaya, Mojokerto, and Sidoarjo. There are limitations of officers. Lack of understanding of immigration law by foreigners. Lack of information obtained from the public regarding the existence of foreigners. Lack of openness on the part of the company where the foreigner works. The efforts made by the Surabaya Special Class I Immigration Office in supervising foreigners are to conduct direct field surveillance to find out the whereabouts of foreigners. Attend KOMINDA (Komunitas Intelejen Daerah: Regional Intelligence Community) activities organized by the Regional Government. Conducting socialization programs to foreigners and the community. Conducting administrative supervision.